Work-Family Balance and Remote Working among Women in Nigeria during Covid-19 Pandemic - Okolie, Ugo Chuks (Universitas Pendidikan Indonesia, 2024)
Organisations face the challenge of establishing ways to mitigate the negative effects of work during coronavirus or Covid-19 pandemic. As a result work-family balance was disrupted and negatively affected the employees’ well-being especially working women. Against this backdrop, this study examined work-family balance of women working from home during covid-19 pandemic. Cross sectional research design was employed and data were collected via a survey of 126 from medical, education, banking, and finance and service sectors in Nigeria. The 126 women were selected using simple random sampling technique and data collected was analysed using simple percentage. The study revealed that women were satisfied by working remotely during the Covid-19 pandemic. The study recommends among others that organisations and government should develop and implement work-family balance policies that would promote the increasing use of remote working arrangement with special reference to working women.